1997
DOI: 10.1007/bfb0119235
|View full text |Cite
|
Sign up to set email alerts
|

The chemistry and biology of fatty acid, polyketide, and nonribosomal peptide biosynthesis

Abstract: Polyketide synthases, fatty acid synthases, and non-ribosomal peptide synthetases are a structurally and mechanistically related class of enzymes that catalyze the synthesis of biopolymers in the absence of a nucleic acid or other template. These enzymes utilize the common mechanistic feature of activating monomers for condensation via covalently-bound thioesters of phosphopantetheine prosthetic groups. The information for the sequence and length of the resulting polymer appears to be encoded entirely within t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 200 publications
0
30
0
Order By: Relevance
“…in CarB assays implies the condensation and cyclization processes precede hydrolysis. Mechanistic studies on thioester hydrolysis are of interest both for the crotonase superfamily and in the wider context of polyketide, fatty acid and non-ribosomal peptide biosynthesis (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…in CarB assays implies the condensation and cyclization processes precede hydrolysis. Mechanistic studies on thioester hydrolysis are of interest both for the crotonase superfamily and in the wider context of polyketide, fatty acid and non-ribosomal peptide biosynthesis (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] These are usually characterised by nuclear magnetic resonance (NMR) spectroscopy, a process that requires the growth of large quantities of bacterial culture and purification of milligram quantities of analyte. The large number of samples that may be expected from combinatorial experiments will require a faster, more sensitive analysis for preliminary screening and structure determination.…”
Section: Received 21 May 1999; Revised 22 June 1999; Accepted 23 Junementioning
confidence: 99%
“…Gene clusters of several bacterial and fungal polyketide pathways have been cloned and analyzed. Sequence analysis has revealed that polyketide synthases (PKSs) 1 are multifunctional enzymes that are structurally and mechanistically related to fatty acid synthases. Through a catalytic process involving repeated decarboxylative condensations between coenzyme A-derived acylthioesters, they synthesize a growing carbon chain backbone that is regio-and stereoselectively modified into the final natural product.…”
mentioning
confidence: 99%